2021
DOI: 10.3390/rs13091645
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Near-Infrared Permanent Laser Scanning Intensity for Retrieving Soil Moisture on a Coastal Beach: Calibration Procedure Using In Situ Data

Abstract: Anthropogenic activities and climate change in coastal areas require continuous monitoring for a better understanding of environmental evolution and for the implementation of protection strategies. Surface moisture is one of the important drivers of coastal variability because it highly affects shoreward sand transport via aeolian processes. Several methods have been explored for measuring surface moisture at different spatiotemporal resolutions, and in recent years, light detection and ranging (LiDAR) technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Several studies have shown that remote sensing data on coastal environments are affected by variables such as wind condition and surface roughness. This has been shown independently for both PLS [ 10 , 15 , 16 ] and SAR data, where the backscattering behaviour depends on the roughness in relation to the wavelength [ 32 , 33 ] and is affected by wind speed and direction [ 34 ]. Therefore, notably, meteorological conditions in terms of wind speed and direction, rain, and surface roughness, will be taken into consideration in the evaluation of the correlation between PLS and SAR data.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several studies have shown that remote sensing data on coastal environments are affected by variables such as wind condition and surface roughness. This has been shown independently for both PLS [ 10 , 15 , 16 ] and SAR data, where the backscattering behaviour depends on the roughness in relation to the wavelength [ 32 , 33 ] and is affected by wind speed and direction [ 34 ]. Therefore, notably, meteorological conditions in terms of wind speed and direction, rain, and surface roughness, will be taken into consideration in the evaluation of the correlation between PLS and SAR data.…”
Section: Introductionmentioning
confidence: 94%
“…Among its applications, forestry [ 1 , 2 , 3 ], river systems [ 4 , 5 ] and geomorphology [ 6 , 7 ] have been investigated. In recent years, our knowledge on coastal environments has been enriched by information provided by TLS systems, which show significant potential for examining coastal processes [ 8 , 9 , 10 ]. Among the coastal applications, TLS has been used in order to generate Digital Elevation Models (DEM) and to evaluate accurate volumetric changes on beaches, dunes and cliffs, Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical remote sensing techniques are based on the principle that wet sand is less reflective than dry sand, due to pore water surrounding the sand grains [24]. Their potential for aeolian research was demonstrated by [25][26][27][28] and while widely used, these techniques are susceptible to cloud, rain, and light conditions. This is not convenient in areas with high average annual cloud cover.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common characterizations of surface roughness is its root-mean-squared height (RMSH). For this purpose, Terrestrial Laser Scanning (TLS) has been investigated for its huge potential for coastal processes [25,50], as it allows fast and repeatable measurements of surface topography [23] and surface moisture. Several studies demonstrated how soil roughness can be evaluated using TLS [51,52].…”
Section: Introductionmentioning
confidence: 99%